Phakic anterior chamber intraocular lens removal with simultaneous posterior chamber phakic intraocular lens implantation and Descemet membrane endothelial keratoplasty - Jorge L. Alioì del Barrio; Ronald Steven II Medalle; Matteo Pederzolli (Taiwan Journal of Ophthalmology, 2024)
The purpose of this study was to describe a case and clinical course of simultaneous anterior chamber phakic intraocular lens (AC-pIOL) removal, implantation of a posterior chamber phakic intraocular implantable collamer lens (ICL), and Descemet membrane endothelial keratoplasty (DMEK). This was a case report of a 44-year-old male with a unilateral decompensated cornea from a displaced Duet–Kelman lens on his left eye that underwent pIOL extraction and implantation of a posterior chamber phakic intraocular ICL and simultaneous DMEK. After 6 months, the cornea of the left eye had regained clarity, the Descemet membrane was graft stable, and the ICL implanted was centered with good vault. Postoperative anisometropia was avoided. There was no development of cataracts or other complications. The simultaneous pIOL extraction, ICL implantation, and DMEK in our case showed good results with full restoration of anterior segment anatomy and return of transparency of the cornea. The current case shows the feasibility of the simultaneous approach instead of sequential as an alternative for patients with endothelial disease associated with AC pIOLs, restoring vision and anatomy and also avoiding postoperative anisometropia.